Quantum-chemical investigation on the pre-nucleation cluster formation between oxalic acid conformers and atmospheric nucleation precursors - Carvalho, Eduardo da Silva (Universidade Federal do Amazonas, 2025)
Aerosol particles formed in the Earth’s troposphere through the nucleation process have large impact on the planet’s radiative balance, cloud formation and precipitation patterns. The growing concerns about the climate change occurring in different parts of the world serve as a motivation for the scientific community to study the formation processes and physicochemical properties of atmospheric aerosols. Oxalic acid is one of the simplest naturally occurring dicarboxylic acid that is abundantly found in the atmosphere, and it has several stable structural conformers. Hydrogen-bonded interactions of oxalic acid with other atmospheric molecules are important as they might influence the chemical composition of the atmosphere, thereby impacting atmospheric chemistry and environmental processes. In this work, we used Density Functional calculations with the M06-2X/6-311++G(3df,3pd) model to examine the interaction of different oxalic acid conformers with sulfuric acid and ammonia — two widely recognized atmospheric nucleation precursor molecules — with the aim of observing the hydrogen bonding characteristics of the conformers individually. An extensive and systematic quantum-chemical calculation has been conducted to analyze the structural, thermodynamical, electrical, and spectroscopic characteristics of several binary and ternary clusters mediated by five oxalic acid conformers. Our analysis of the electronic binding energies and free energy changes associated with the formation of clusters and its population distribution at ambient temperature reveals that multiple conformations of oxalic acid have the potential to engage in stable cluster formation in the atmosphere. In fact, the highest energy oxalic acid conformer contributes most significantly to the population distribution of the clusters. According to the present calculations, clusters of oxalic acid with sulfuric acid demonstrate greater thermodynamic stability, a higher probability of formation, and more intense light scattering compared to clusters with ammonia. Furthermore, the analysis of successive cluster formation reveals that clusters formed between sulfuric acid and oxalic acid are more likely to grow spontaneously than those formed between ammonia and oxalic acid.